The influence of unparallelism of the distance measuring device axis during cadastre measurements - Bagdžiūnaitė, Renata (Geodesy and Cartography, 2012)
Investigation of influence of the geometric parameters accuracy in the distance measuring device is presented by the method. The case when working without the prism reflector is analysed assessing the different parameter between the main axis of the distance measuring device under different circumstances of measurement. The investigation of influence of the geometric parameters accuracy is performed according to the method proposed. The calculations were carried out by using the data from former investigations. The influence of unparallelism of the distance measuring instrument is investigated by simulating the structures’ cadastre measurements working without prism reflector and having various angles of declination between the plane of sightseeing and the sight line.Article in Lithuanian.Tolimačio geometrinių parametrų tikslumo įtakos matuojant statybos objektus tyrimasSantrauka. Darbe modeliavimo būdu tiriama tolimačio ašių nelygiagretumo įtaka atliekant matavimus statybos aikštelėse, kai dirbama be prizminio reflektoriaus, esant skirtingiems parametrams tarp pagrindinių tolimačio ašių bei įvairioms matavimų s ąlygoms. Ašių nelygiagretumo įtaka tiriama pagal jau taikomą ir pagal mūsų pasiūlytą metodikas. Skaičiavimai atlikti panaudojus ankstesnių tyrimų duomenis.Raktažodžiai: atstumo pataisa, vizavimo ašies nuokrypis, horizontalusis necentriškumas, vertikalusis necentriškumas.First published online: 03 Aug 2012